High-toughness free-cutting ferritic stainless steel and method for producing the same
Patent Information
- Application Number
- CN202311793052.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-12-25
AI Technical Summary
[0010]本发明解决的技术问题是:1)显著提高铁素体不锈钢的强度和塑韧性;2)有效改善高强度铁素体不锈钢车削性能;3)减轻铁素体不锈钢组织不均匀性;4)降低经济成本压力
[0032]1、经本发明设计生产的高强韧性易切削铁素体不锈钢,室温环境下具有非常优异力学性能,其中抗拉强度可达600~620MPa,屈服强度为420~450MPa,断后伸长率25.0%~27.0%,断面收缩率55%~57%,硬度为190~210HBW。
Smart Images

Figure CN117737591B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of ferritic stainless steel bar and wire production, and in particular relates to a high-strength and tough free-machining ferritic stainless steel and its preparation method. Background Technology
[0002] Stainless steel has a wide range of applications, playing a significant role not only in aerospace and petrochemical industries, but also in transportation infrastructure, kitchenware, household appliances, and building materials. However, my country currently faces a shortage of nickel resources and rising prices, which severely restricts the development of austenitic stainless steel. Compared to austenitic stainless steel, ferritic stainless steel requires very low or even no nickel content, making it more affordable. Ferritic stainless steel exhibits a low coefficient of thermal expansion, excellent thermal conductivity, and good resistance to pitting and stress corrosion corrosion even in challenging environments. Currently, the microstructure and mechanical properties of conventional ferritic stainless steel are difficult to control, limiting its production and wider application. Therefore, the current production and consumption of ferritic stainless steel are not optimistic, accounting for only about one-fifth of total stainless steel consumption. Thus, there is an urgent need to develop ferritic stainless steels with excellent comprehensive mechanical properties and good processing performance, which is crucial for increasing the market share of ferritic stainless steel.
[0003] Numerous studies have been conducted both domestically and internationally on improving the mechanical properties of ferritic stainless steel. Table 1 shows the domestic and international patents for high-strength ferritic stainless steel, along with their corresponding main chemical compositions and product characteristics.
[0004] Table 1. Domestic and international patents for high-strength ferritic stainless steel and their corresponding main chemical compositions and product characteristics.
[0005]
[0006]
[0007] Table 1 (Continued) shows domestic and international patents for high-strength ferritic stainless steel and their corresponding main chemical compositions and product characteristics.
[0008]
[0009] In Table 1 and its continuation, patents numbered 1 to 3 disclose methods to improve the strength or toughness of ferritic stainless steel by adding single or combined elements of vanadium (V), niobium (Nb), titanium (Ti), and copper (Cu). The mechanism involves adding vanadium to the steel, utilizing the fact that V has a greater affinity for C than for Cr, thus easily forming VC and difficult to form Fe. 23C6 improves the corrosion resistance of ferritic stainless steel while utilizing the precipitation strengthening effect of VC. The principle is to pin the austenite grain boundaries, prevent the recrystallization of deformed austenite, increase the austenite incubation period, and significantly improve the strength of the material. Nb and Ti, as strong carbon-fixing elements, can also improve the strength and hardness of the material by controlling their addition. In addition, the formation of TiN, Nb (C, N) and other precipitates in the molten steel can be distributed in the molten steel as heterogeneous nucleation particles, which greatly increases the equiaxed / columnar crystal ratio of the continuously cast billet, thereby refining the microstructure of the rolled material and helping to improve the comprehensive mechanical properties of the material. The addition of a small amount of copper to stainless steel can significantly improve the plasticity of the material. In addition, related patents indicate that when the Cu content is controlled at 0.08-1.50%, the Cu solid solution strengthening effect can play its maximum role. When Cu ≥ 1.5 × Nb%, more Cu dissolves in the steel, improving the strength and plasticity of the steel. Patent No. 4 discloses an improvement in the impact performance of ferritic stainless steel at room temperature by controlling the microstructure of the matrix through rolling and heat treatment processes. However, this patent does not address whether increasing the strength of ferritic stainless steel can simultaneously improve its toughness at negative temperatures, thus failing to truly address the issue of the high ductile-brittle transition temperature of ferritic stainless steel. Furthermore, it involves the addition of numerous expensive alloying elements, significantly increasing economic costs. Therefore, this invention is proposed. The key feature of this invention is the effective improvement of the strength of ferritic stainless steel while reducing the ductile-brittle transition temperature through the regulation of chemical elements such as C, N, and S, and optimization of the heat treatment process. It also reduces or even eliminates the use of expensive alloying elements, demonstrating extremely high economic applicability. Summary of the Invention
[0010] The technical problems solved by this invention are: 1) significantly improving the strength and toughness of ferritic stainless steel; 2) effectively improving the machinability of high-strength ferritic stainless steel; 3) reducing the inhomogeneity of the microstructure of ferritic stainless steel; and 4) reducing economic cost pressure. To solve the above technical problems, this invention provides a high-strength, high-toughness, free-machining ferritic stainless steel and its preparation method.
[0011] This invention, through the design of C and N element content and optimization of heat treatment processes, results in a matrix with dispersed spherical carbides and uniformly distributed ferrite, significantly improving the strength and toughness of ferritic stainless steel. Specifically, the room temperature tensile strength reaches 600–620 MPa, the yield strength is 420–450 MPa, the elongation after fracture is 25.0%–27.0%, the reduction of area is 55%–57%, and the hardness is 190–210 HBW. Furthermore, the impact absorption energy A at -20℃ is also significant. KV≥39J, shear cross-sectional area at -40℃ ≥55%, ductile-brittle transition temperature reduced from 0℃ to -40℃. The addition of sulfur in this invention not only improves the machinability of the material, but also, the uniform distribution of a large number of sulfides in the matrix enhances the uniformity of the room-temperature microstructure, optimizes the stability of the material's mechanical properties, and greatly expands the application of ferritic stainless steel in the automotive, chemical, and home appliance industries.
[0012] To achieve the above objectives, the present invention adopts the following technical solution.
[0013] This invention provides a high-strength and high-toughness free-machining ferritic stainless steel, wherein the chemical composition of the stainless steel, by weight percentage, comprises: C: 0.10%–0.15%, Si ≤ 1.00%, Mn ≤ 1.5%, P ≤ 0.04%, S: 0.15%–0.25%, Cr: 15.50%–16.50%, Mo: 0.20%–0.60%, N ≤ 0.06%, with the remainder being iron and unavoidable impurities.
[0014] Preferably, the high-strength and tough free-machining ferritic stainless steel contains the following chemical composition by weight percentage: C: 0.120%–0.150%, Si: 0.20%–0.50%, Mn: 1.20%–1.40%, P≤0.028%, S: 0.20%–0.23%, Cr: 16.10%–16.50%, Mo: 0.22%–0.30%, N: 0.035%–0.055%, with the remainder being iron and unavoidable impurities.
[0015] The present invention also provides a method for preparing the above-mentioned high-strength and tough free-machining ferritic stainless steel, comprising the following steps: electric arc furnace smelting → AOD furnace smelting → LF furnace refining → continuous casting → rolling → annealing. The steel material is successively smelted in an electric arc furnace, refined in an AOD furnace, and refined in an LF furnace to obtain molten steel with the target composition. The molten steel is then turned into a continuously cast billet using a continuous casting machine. The continuously cast billet is then rolled and annealed to obtain the stainless steel wire rod.
[0016] Preferably, during the electric arc furnace smelting process, scrap stainless steel with low P and low levels of the five harmful elements (Pb, Sn, As, Sb, Bi) is selected as the steel material, and the P content of the tapped steel is controlled to be ≤0.028% to obtain crude steel.
[0017] Preferably, the AOD furnace smelting process includes: adding molten steel smelted in an electric arc furnace to the AOD furnace, followed by the addition of chilled lime; employing top and bottom combined oxygen blowing for heating and decarburization, with a target C content of 0.05%–0.08%; reducing the slag by adding ferrosilicon and ferromanganese alloy, while fluorite can be added to improve slag fluidity, controlling the slag basicity R at 1.5–2.0; finally, based on the target sulfur content of 0.15%–0.25% and the ferrosulfide yield (60%–70%), adding ferrosulfide alloy to the molten steel, with a target tapping temperature of 1630–1650°C. More preferably, 1000–1200 kg of chilled lime and 300–350 kg of ferrosulfide alloy are added.
[0018] Preferably, the LF furnace refining process includes: after the AOD-smelted molten steel arrives at the station, the Ar gas flow rate is adjusted; once the slag becomes fluid, samples are taken and the temperature is measured; based on the sample results, alloys are added to finely adjust the composition of the molten steel to obtain the target molten steel; subsequently, bottom soft blowing of argon gas lasts for ≥5 minutes to allow inclusions to float sufficiently; finally, the ladle temperature is controlled at 1630–1650℃. More preferably, the added alloys are selected from micro-carbon ferrochrome, ferrosulfide, and silicon-manganese alloys.
[0019] Preferably, the continuous casting process improves the billet microstructure by controlling the superheat, thereby optimizing the hot-rolled microstructure. However, free-machining stainless steel billets often suffer from severe defects such as subcutaneous bubbles, which can easily lead to billet cracking during rolling and affect yield. Therefore, to ensure that the as-cast sulfides are mostly Type I sulfides and that subcutaneous bubbles rise to the molten steel, the continuous casting cooling regime is "weak cooling." More preferably, the target superheat for the continuous casting process is 30–50°C, the casting speed is set at 0.7–0.9 m / min, and the crystallizer water flow rate is set at 92–95 m³ / min. 3 / h, the set value of water flow rate in the foot roller section is 2.0~3.5m³ / h. 3 / h, the set value for the clamping section water flow rate is 1.9~2.5m³ / h. 3 / h. More preferably, the target molten steel obtained from LF furnace refining is continuously cast into a continuously cast square billet using an arc-shaped progressive straightening continuous casting machine.
[0020] Preferably, in the rolling process of free-cutting ferritic stainless steel wire rod, it is necessary to ensure that the initial rolling temperature is set correctly to avoid cracking caused by cooling during rolling and to achieve the target hot-rolled wire rod microstructure. Rapid cooling after rolling induces a significant transformation of austenite to martensite in the matrix, providing a prerequisite for subsequent heat treatment adjustments. More preferably, the initial rolling temperature is set to 1180–1200°C. Rough rolling employs head-side water-avoidance rolling, and the wire rod is coiled using a Garrett coiler. After being transferred from the coil, the wire rod is water-cooled to room temperature to obtain the hot-rolled wire rod. More preferably, various common specifications can be rolled.
[0021] Preferably, the annealing process improves the degree of martensite decomposition and carbide spheroidization by adjusting the heat treatment temperature and holding time. More preferably, the hot-rolled ferritic stainless steel wire rod is rapidly heated to 720-760°C at a rate of 10-15°C / min and held for 180-240min, then cooled to 650°C or below at a controlled rate of 50-70°C / h. After that, the inner cover and cooling cover are removed, and the wire rod is air-cooled and exits the furnace.
[0022] The role of each chemical component and the design principles in this invention are explained below.
[0023] Carbon (C) and nitrogen (N): As the main austenite-forming elements, carbon and nitrogen can significantly increase the content of high-temperature austenite in stainless steel with the increase of carbon and nitrogen content, so that γ→α phase transformation occurs during cooling, which helps to refine coarse ferrite grains. After heat treatment adjustment, the room temperature microstructure of ferritic stainless steel is fully improved, and the strength and toughness are effectively improved. The carbon content of this invention is controlled at 0.10~0.15%, and the nitrogen content is controlled at ≤0.06%.
[0024] Silicon (Si): Silicon is a strong deoxidizer, reducing the oxygen content in steel and improving inclusions. However, high silicon content can also reduce the cold workability of stainless steel, and affect its plasticity and resistance to chloride ion corrosion. Therefore, the silicon content in this invention is controlled at ≤1.00%.
[0025] Manganese (Mn): Manganese is an austenite-forming element. In steel, manganese readily combines with sulfur to form manganese sulfide, which effectively improves the hot brittleness of high-sulfur free-machining stainless steel caused by the formation of a large amount of iron sulfide at the grain boundaries. In addition, manganese sulfide inclusions can act as stress concentration sources during machining, reducing cutting forces and effectively improving machining performance. Therefore, the manganese content in this invention is controlled at ≤1.5%.
[0026] Phosphorus (P): Phosphorus is a harmful element in steel, causing steel to become brittle at cold. In this invention, the phosphorus content is controlled at ≤0.04%.
[0027] Sulfur (S): Sulfur is a harmful element for ordinary stainless steel, but as a typical free-machining element, sulfur easily forms manganese sulfide inclusions with manganese (Mn) in steel. The morphology of these inclusions is key to improving machinability. The mechanism is that when the material is being turned, the inclusions become stress gaps, reducing cutting resistance. At the same time, manganese sulfide inclusions can also lubricate the cutting tool. In addition, sulfides effectively improve the coarseness of the microstructure of ferritic stainless steel and improve its plasticity and toughness. Therefore, the sulfur content in this invention is controlled at 0.15% to 0.25%.
[0028] Chromium (Cr): Chromium is the main element in stainless steel. When the chromium content in steel exceeds 10.5%, a passivation film will form on the surface, which will hinder the further occurrence of oxidation reaction, thus giving stainless steel significant corrosion resistance. As the chromium content in stainless steel increases, the pitting corrosion sites of stainless steel increase and the corrosion resistance is improved. Therefore, the chromium content in this invention is controlled at 15.50% to 16.50%.
[0029] Molybdenum (Mo): As an important element in ferritic stainless steel, the main function of molybdenum is to improve the corrosion resistance of ferritic stainless steel together with chromium, especially to improve the resistance to pitting corrosion and crevice corrosion. Therefore, the molybdenum content in this invention is controlled at 0.20% to 0.60%.
[0030] The high-strength and toughness free-machining ferritic stainless steel of this invention achieves its goal of increasing the austenite ratio and refining coarse ferrite through phase transformation by optimizing the C and N composition, adding S element, and heat treatment process. After heat treatment, the matrix is adjusted to obtain tempered sorbite + ferrite, resulting in high strength and hardness at room temperature, as well as excellent ductility and toughness. Furthermore, the sulfur and manganese contents are specified, and manganese sulfide inclusions are used to pin the coarse austenite grains, effectively delaying the deformation austenite recrystallization behavior, significantly improving the material's overall mechanical properties and machinability, ensuring excellent cold working performance and successful service worldwide. This material is mainly used in automotive airbag inflator brackets, achieving domestic production of the material and possessing broad market application prospects.
[0031] Compared with the prior art, the high-strength and high-toughness free-machining ferritic stainless steel of the present invention has the following significant advantages:
[0032] 1. The high-strength and high-toughness free-machining ferritic stainless steel designed and produced by this invention has excellent mechanical properties at room temperature, including tensile strength of 600-620 MPa, yield strength of 420-450 MPa, elongation after fracture of 25.0%-27.0%, reduction of area of 55%-57%, and hardness of 190-210 HBW.
[0033] 2. The high-strength and high-toughness free-machining ferritic stainless steel designed and produced by this invention possesses excellent low-temperature impact performance, with an impact absorption energy A at -20℃. KV ≥39J, shear cross-sectional area at -40℃ ≥55%, ductile-brittle transition temperature decreases from 0℃ to -40℃.
[0034] 3. The high-strength and tough free-machining ferritic stainless steel designed and produced by this invention has excellent turning performance. The surface roughness of the sample after turning is ≤1.40μm, the chips are easily broken, and the proportion of "C" shaped chips is as high as 70% to 80%. The main turning force is ≤137N, and the turning performance is comparable to that of Japanese standard SUS430F.
[0035] 4. The high-strength and tough free-machining ferritic stainless steel produced by the present invention has a uniform transverse grain size finer than grade 10. Attached Figure Description
[0036] Figure 1 The image shows the macroscopic morphology of the impact fracture surface of a stainless steel -40℃ "V" notch specimen from Example 2 of this invention.
[0037] Figure 2 The macroscopic morphology of the impact fracture surface of the comparative example SUS430F stainless steel “V” notch specimen at -40℃ is shown in this invention.
[0038] Figure 3 This is a chip morphology diagram from a stainless steel turning experiment of Embodiment 2 of the present invention.
[0039] Figure 4 The image shows the chip morphology from a comparative example of this invention, SUS430F stainless steel, during a turning experiment.
[0040] Figure 5 This is the transverse microstructure distribution of stainless steel at room temperature in Example 2 of the present invention.
[0041] Figure 6 The image shows the transverse microstructure distribution of SUS430F stainless steel at room temperature, which is a comparative example of this invention. Detailed Implementation
[0042] To facilitate understanding, the technical solutions and implementation methods of the present invention will be further described clearly, completely, and in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the embodiments described herein are implemented based on the technical solutions of the present invention, providing detailed implementation methods and specific operating procedures, but are only some embodiments of the present invention, not all embodiments. The specific implementation methods described are limited to illustrating and explaining the present invention and do not limit the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0043] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used in the examples are commercially available unless otherwise specified.
[0044] Example 1
[0045] The composition and mass fraction of the high-strength and tough free-machining ferritic stainless steel in this embodiment are shown in Table 1.
[0046] In this embodiment, the high-strength and tough free-machining ferritic stainless steel is manufactured using the following method: electric arc furnace smelting → AOD refining → LF refining → continuous casting → rolling → annealing, as detailed below:
[0047] (1) Electric arc furnace smelting: The electric arc furnace melts scrap steel. Low P and low five harmful elements (Pb, Sn, As, Sb, Bi) scrap stainless steel are selected. The target crude steel P ≤ 0.028%, and the actual value is 0.027%.
[0048] (2) AOD refining: The crude steel smelted in the electric arc furnace is added to the AOD furnace, followed by 1000 kg of cold lime. Top and bottom oxygen blowing is used to raise the temperature and decarburize. The target C content is 0.05% to 0.08%, and the actual value is 0.066%. Ferrosilicon and ferromanganese alloy are added for reduction. At the same time, fluorite is added to improve the slag fluidity. The slag basicity is controlled at R between 1.5 and 2.0, and the actual value is 1.63. Finally, according to the target sulfur content of 0.15% to 0.25% and the ferrosulfide yield (60% to 70%), 300 to 350 kg of ferrosulfide alloy is added to the molten steel. The actual ferrosulfide is 340 kg, and the actual sulfur content is 0.213%. The target tapping temperature is 1630 to 1650℃, and the actual value is 1634℃.
[0049] (3) LF refining: After the AOD smelting molten steel arrives at the station, adjust the Ar gas flow rate. When the slag becomes fluid, take a sample and measure the temperature. Based on the sample results, add alloy to finely adjust the molten steel composition to obtain the target molten steel. Then, the bottom soft blowing argon time is ≥5min, the actual value is 7min, so that the inclusions float up fully. Finally, control the ladle temperature at 1630~1650℃, the actual value is 1635℃.
[0050] (4) Continuous Casting: The target molten steel obtained from LF refining is continuously cast using an arc-shaped progressive straightening continuous casting machine. The target superheat during continuous casting is 30-50℃, with an actual value of 32-45℃. To ensure that the as-cast sulfide morphology consists of more Type I sulfides and that the subsurface bubbles of the sulfur-containing steel rise to the molten steel, the continuous casting cooling regime is "weak cooling". The casting speed is set at 0.7-0.9 m / min, with an actual value of 0.72-0.85 m / min, and the crystallizer water flow rate is set at 92-95 m³ / min. 3 / h, actual value is 92.3~94.5m 3 / h, the set value of water flow rate in the foot roller section is 2.0~3.5m³ / h. 3 / h, actual value is 2.2~3.4m 3 / h, the set value for the clamping section water flow rate is 1.9~2.5m³ / h. 3 / h, actual value is 1.9~2.35m 3 / h.
[0051] (5) Wire rod rolling: The continuously cast billets produced above are heated in a roller hearth furnace, with the initial rolling temperature set at 1180–1200℃ and the actual temperature at 1195℃. The rolling specifications are as follows: Wire rod is rough-rolled using a head-end water-avoiding rolling process. The wire rod is then coiled via a Garrett coiler and subsequently water-cooled after being transferred from the line. Various common specifications can be achieved, including the following specifications: The performance requirements of the finished product are the highest at this stage, and the product enterprise standards are formulated based on this principle in this invention.
[0052] (6) Heat treatment process: The ferritic stainless steel wire rods obtained above are annealed in a bell-type annealing furnace. The wire rods are rapidly heated to 720°C at a rate of 10°C / min. After holding at 720°C for 180min, a cooling hood is placed and the wire rods are cooled to 650°C at a rate of 50°C / h. Then the inner hood and the cooling hood are removed, and the wire rods are air-cooled and taken out of the furnace.
[0053] Example 1: The composition meets the control requirements, as detailed in Table 1. The wire rod yield is 96.4%. After heat treatment, the wire rod was tested and found to have a room temperature tensile strength of 619 MPa, a yield strength of 443 MPa, an elongation after fracture of 25.5%, a reduction of area of 56.0%, and a hardness of 209 HBW. In the negative temperature brittleness test, the impact absorption energy A at -20℃ was... KV It is 43.7 J, shear ratio 75%, and impact absorption energy A at -40℃. KV The J is 36.9, the shear cross-sectional area is 64%, and the ductile-brittle transition temperature is -40℃. In the turning performance test, the surface roughness after turning was 1.39μm, the proportion of "C"-shaped chips was 80%, and the main cutting force was 137N. The main mechanical properties are shown in Tables 2 and 3, and the turning performance evaluation is shown in Table 4.
[0054] Example 2
[0055] The composition and mass fraction of the high-strength and tough free-machining ferritic stainless steel in this embodiment are shown in Table 1.
[0056] In this embodiment, the high-strength and tough free-machining ferritic stainless steel is manufactured using the following method: electric arc furnace smelting → AOD refining → LF refining → continuous casting → rolling → annealing, as detailed below:
[0057] (1) Electric arc furnace smelting: The electric arc furnace melts scrap steel. Low P and low five harmful elements (Pb, Sn, As, Sb, Bi) scrap stainless steel are selected. The target crude steel P ≤ 0.028%, and the actual value is 0.0261%.
[0058] (2) AOD refining: The crude steel smelted in the electric arc furnace is added to the AOD furnace and then 1000 kg of cold lime is added. Top and bottom oxygen blowing is used to raise the temperature and decarburize. The target C content is 0.05% to 0.08%, and the actual value is 0.058%. Ferrosilicon and ferromanganese alloy are added for reduction. At the same time, fluorite is added to improve the slag fluidity. The slag basicity R is controlled at 1.5 to 2.0, and the actual value is 1.67. Finally, according to the target sulfur content of 0.15% to 0.25% and the ferrosulfide recovery rate (60% to 70%), 300 to 350 kg of ferrosulfide alloy is added to the molten steel. The actual ferrosulfide is 350 kg, the actual sulfur content is 0.219%, the target tapping temperature is 1630 to 1650℃, and the actual value is 1641℃.
[0059] (3) LF refining: After the AOD smelting molten steel arrives at the station, adjust the Ar gas flow rate. When the slag becomes fluid, take a sample and measure the temperature. Based on the sample results, add alloy to finely adjust the molten steel composition to obtain the target molten steel. Then, the bottom soft blowing argon time is ≥5min, the actual value is 8min, so that the inclusions float up fully. Finally, control the ladle temperature at 1630~1650℃, the actual value is 1633℃.
[0060] (4) Continuous casting: The target molten steel obtained from LF refining is continuously cast using an arc-shaped progressive straightening continuous casting machine. The target superheat during continuous casting is 30-50℃, and the actual value is 31-43℃. To ensure that the as-cast sulfide morphology is more type I sulfides and to ensure that the subsurface bubbles of sulfur-containing steel rise to the molten steel, the continuous casting cooling regime is "weak cooling". The casting speed is set at 0.7-0.9 m / min, and the actual value is 0.71-0.87 m / min. The crystallizer water flow rate is set at 92-95 m³ / min. 3 / h, actual value is 92.2~94.5m 3 / h, the set value of water flow rate in the foot roller section is 2.0~3.5m³ / h. 3 / h, actual value is 2.1~3.25m 3 / h, the set value for the clamping section water flow rate is 1.90~2.50m³ / h. 3 / h, actual value is 2.0~2.37m 3 / h.
[0061] (5) Wire rod rolling: The continuously cast billets produced above are heated in a roller hearth furnace, with the initial rolling temperature set at 1180–1200℃ and the actual temperature at 1189℃. The rolling specifications are as follows: For wire rod, roughing is carried out using head-side water-avoiding rolling, and the wire rod is coiled through a Garrett coiler. After being transferred, the wire rod is cooled in water after leaving the production line.
[0062] (6) Heat treatment process: The ferritic stainless steel wire rods obtained above are annealed in a bell-type annealing furnace. The wire rods are rapidly heated to 740°C at a rate of 10°C / min. After holding at 740°C for 180min, a cooling hood is placed and the wire rods are cooled to 650°C at a rate of 50°C / h. Then the inner hood and the cooling hood are removed, and the wire rods are air-cooled and taken out of the furnace.
[0063] Example 2: The composition met the control requirements, as detailed in Table 1. The wire rod yield was 96.7%. After heat treatment, the wire rod was tested and found to have a room temperature tensile strength of 611 MPa, a yield strength of 437 MPa, an elongation after fracture of 26.0%, a reduction of area of 56.0%, and a hardness of 201 HBW. In the negative temperature brittleness test, the impact absorption energy A at -20℃ was... KV It is 41.5 J, shear ratio 71%, and impact absorption energy A at -40℃. KV The J is 35.3, the shear cross-sectional area is 62%, and the ductile-brittle transition temperature is -40℃. In the turning performance test, the surface roughness after turning was 1.31μm, the proportion of "C"-shaped chips was 78%, and the main cutting force was 133N. The main mechanical properties are shown in Tables 2 and 3, and the turning performance evaluation is shown in Table 4.
[0064] Using the SUS430F as a comparison, relevant performance tests were conducted. The following analysis, combined with the attached... Figure 1-6 This invention provides a comparative analysis of the main mechanical and machinability properties of stainless steel from Example 2 and comparative example SUS430F, with additional details provided. Figure 1 The macroscopic morphology of the impact fracture surface of a stainless steel "V"-shaped specimen at -40℃, produced in Example 2, is shown in the figure. The impact fracture surface morphology is "chisel-shaped," exhibiting typical ductile characteristics, indicating that no ductile-brittle transition occurred. According to Appendix C of standard GB / T229-2020, the shear fraction at -40℃ is 65%, indicating that the material did not undergo a ductile-brittle transition at this temperature. Figure 2 The image shows the macroscopic morphology of the impact fracture surface of a "V"-shaped specimen of SUS430F stainless steel at -40℃. It can be observed from the figure that there is no obvious macroscopic plastic deformation on the impact fracture surface, the fracture surface is flat, and typical brittle fracture morphology such as cleavage fracture steps and river patterns are observed, indicating that the ductile-brittle transition phenomenon has occurred.
[0065] Appendix Figure 3 The attached image shows the chip morphology of the stainless steel turning experiment in Example 2. Figure 4 To illustrate the chip morphology from the turning experiment of SUS430F stainless steel as a comparative example, from... Figure 3 and Figure 4 Comparing the chip morphology images from the turning experiment, it can be seen that both have a high proportion of "C" shaped chips, indicating that the chips are easy to clean during turning.
[0066] Appendix Figure 5The figure shows the transverse microstructure distribution of stainless steel in Example 2. It can be observed that the room temperature microstructure of Example 2 is uniform and fine, without any coarse ferrite structure. Its grain size rating is finer than 10, which helps improve the overall mechanical properties of the material. (See attached figure.) Figure 6 To illustrate the transverse microstructure distribution of SUS430F stainless steel, the figure shows that the core of the comparative SUS430F exhibits unrecrystallized microstructure and coarse ferrite microstructure, which severely degrades the mechanical properties of the material. Its overall grain size rating is 7-8.
[0067] Example 3
[0068] The composition and mass fraction of the high-strength and tough free-machining ferritic stainless steel in this embodiment are shown in Table 1.
[0069] In this embodiment, the high-strength and tough free-machining ferritic stainless steel is manufactured using the following method: electric arc furnace smelting → AOD refining → LF refining → continuous casting → rolling → annealing, as detailed below:
[0070] (1) Electric arc furnace smelting: The electric arc furnace melts scrap steel. The scrap stainless steel with low P and low five harmful elements (Pb, Sn, As, Sb, Bi) is selected. The target crude steel P ≤ 0.028% and the actual value is 0.0254%.
[0071] (2) AOD refining: The crude steel smelted in the electric arc furnace is added to the AOD furnace and then 1000 kg of cold lime is added. Top and bottom oxygen blowing is used to raise the temperature and decarburize. The target C content is 0.05% to 0.08%, and the actual value is 0.067%. Ferrosilicon and ferromanganese alloy are added for reduction. At the same time, fluorite is added to improve the slag fluidity. The slag basicity R is controlled at 1.5 to 2.0, and the actual value is 1.73. Finally, according to the target sulfur content of 0.15% to 0.25% and the ferrosulfide recovery rate (60% to 70%), 300 to 350 kg of ferrosulfide alloy is added to the molten steel. The actual ferrosulfide added is 338 kg, and the actual sulfur content is 0.208%. The target tapping temperature is 1630 to 1650℃, and the actual value is 1637℃.
[0072] (3) LF refining: After the molten steel from the above AOD smelting arrives at the station, adjust the Ar gas flow rate. When the slag becomes fluid, take a sample and measure the temperature. Based on the sample results, add alloys to finely adjust the composition of the molten steel to obtain the target molten steel. Then, the bottom soft blowing argon time is ≥5min, the actual value is 8min, so that the inclusions float up fully. Finally, control the ladle temperature at 1630~1650℃, the actual value is 1644℃.
[0073] (4) Continuous casting: The target molten steel obtained from LF refining is continuously cast using an arc-shaped progressive straightening continuous casting machine. The target superheat during continuous casting is 30-50℃, and the actual value is 30-47℃. To ensure that the as-cast sulfide morphology is more Type I sulfides and to ensure that the subsurface bubbles of sulfur-containing steel rise to the molten steel, the continuous casting cooling regime is "weak cooling". The casting speed is set at 0.70-0.90 m / min, and the actual value is 0.74-0.89 m / min. The crystallizer water flow rate is set at 92-95 m³ / min. 3 / h, actual value is 92.5~94.7m 3 / h, the set value of water flow rate in the foot roller section is 2.0~3.5m³ / h. 3 / h, actual value is 2.0~3.1m 3 / h, the set value for the clamping section water flow rate is 1.9~2.5m³ / h. 3 / h, actual value is 2.0~2.43m 3 / h.
[0074] (5) Wire rod rolling: The continuously cast billets produced above are heated in a roller hearth furnace, with the initial rolling temperature set at 1180–1200℃ and the actual temperature at 1198℃. The rolling specifications are as follows: The wire rod is rough rolled using head-side water-avoidance rolling. After passing through the Garrett coiler, the wire rod is transferred and then water-cooled off the production line.
[0075] (6) Heat treatment process: The ferritic stainless steel wire rods obtained above are annealed in a bell-type annealing furnace. The wire rods are rapidly heated to 760°C at a rate of 10°C / min. After holding at 760°C for 180min, a cooling hood is placed and the wire rods are cooled to 650°C at a rate of 50°C / h. Then the inner hood and the cooling hood are removed, and the wire rods are air-cooled and taken out of the furnace.
[0076] Example 3: The composition meets the control requirements, as detailed in Table 1. The wire rod yield is 96.1%. After heat treatment, the wire rod was tested and found to have a room temperature tensile strength of 604 MPa, a yield strength of 425 MPa, an elongation after fracture of 27.0%, a reduction of area of 57.0%, and a hardness of 196 HBW. In the negative temperature brittleness test, the impact absorption energy A at -20℃ was... KV It is 39.4 J, shear ratio 68%, and impact absorption energy A at -40℃. KV The J is 34.3, the shear cross-sectional area is 55%, and the ductile-brittle transition temperature is -40℃. In the turning performance test, the surface roughness after turning was 1.24μm, the proportion of "C"-shaped chips was 74%, and the main cutting force was 129N. The main mechanical properties are shown in Tables 2 and 3, and the turning performance evaluation is shown in Table 4.
[0077] Table 1 shows the composition (wt%) of the high-strength and tough free-machining ferritic stainless steel prepared in Examples 1-3 and the comparative example SUS430F.
[0078]
[0079] Table 2 shows the room temperature tensile properties of the high-strength and tough free-machining ferritic stainless steels prepared in Examples 1-3 and the room temperature tensile properties of the comparative SUS430F.
[0080]
[0081] Table 3 shows the impact properties of the high-strength and tough free-machining ferritic stainless steels prepared in Examples 1-3 and the comparative SUS430F.
[0082]
[0083]
[0084] Table 4 shows the turning test results of the high-strength and tough free-machining ferritic stainless steels prepared in Examples 1-3 and the turning test results of the comparative example SUS430F.
[0085]
[0086] Based on the above performance test results, and in conjunction with the attached... Figure 1-6 It can be found that the high-strength and tough free-machining ferritic stainless steel produced by this invention has high strength and excellent plasticity at room temperature, and the material meets the service hardness requirements. The tensile strength can reach 600-620MPa, the yield strength is 420-450MPa, the elongation is 25.0%-27.0%, the reduction of area is 55%-57%, and the hardness value is 190-210HBW.
[0087] The high-strength and high-toughness free-machining ferritic stainless steel wire rod produced by this invention possesses excellent low-temperature impact performance, with an impact absorption energy A at -20℃. KV ≥39J, shear cross-sectional area at -40℃ ≥55%, ductile-brittle transition temperature decreases from 0℃ to -40℃.
[0088] The high-strength and tough free-machining ferritic stainless steel wire rod produced by this invention has excellent stability in material mechanical properties. The stability is reflected in: 1) the tensile strength of Examples 1-3 produced by the process required by this invention is consistently higher than 600MPa, without significant deviation from the data; 2) no ductile-brittle transition phenomenon is observed in terms of impact performance.
[0089] The high-strength and tough free-machining ferritic stainless steel wire rod produced by this invention was subjected to a comprehensive evaluation experiment on its turning performance. The results showed that the surface roughness of the material after turning in Examples 1-3 was ≤1.50μm, which was slightly higher than that of the material after turning in the comparative example SUS430F. The chip turning performance of Examples 1-3 was better than that of the comparative example SUS430F. The main turning force value of Examples 1-3 was slightly higher than that of SUS430F. Therefore, the comprehensive turning performance of Examples 1-3 was comparable to that of the Japanese standard SUS430F.
[0090] In summary, the material of this invention, through the design of carbon and nitrogen element compositions, the addition of sulfur, and the optimization of heat treatment processes, achieves a microstructure with tempered sorbite as the base and uniformly distributed ferrite, significantly improving the comprehensive mechanical properties of ferritic stainless steel. The ferritic stainless steel manufactured by this invention exhibits uniform and dispersed sulfide distribution, effectively pinning the original austenite grain boundaries, refining the room temperature microstructure, optimizing microstructure homogeneity, and resulting in excellent machinability after machining, including low surface roughness, good chip breaking effect, and low machining force. The high-strength and high-toughness free-machining ferritic stainless steel manufactured using the composition and process designed in this invention effectively addresses the shortcomings of ferritic stainless steel, such as low strength and poor low-temperature toughness. This material is mainly used in automotive airbag brackets and has already achieved import substitution.
[0091] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Other variations and modifications may be made without departing from the technical solutions described in the claims.
Claims
1. A high-strength and high-toughness free-machining ferritic stainless steel, characterized in that, The chemical composition, by weight percentage, includes C: 0.10%–0.15%, Si ≤ 1.00%, Mn ≤ 1.5%, P ≤ 0.04%, S: 0.15%–0.25%, Cr: 15.50%–16.50%, Mo: 0.20%–0.60%, N ≤ 0.06%, with the remainder being iron and unavoidable impurities. The ferritic stainless steel exhibits a room temperature tensile strength of 600–620 MPa, a yield strength of 420–450 MPa, an elongation after fracture of 25.0%–27.0%, a reduction of area of 55%–57%, and a hardness of 190–210 HBW. Furthermore, in terms of negative temperature impact performance, the impact absorption energy (AKV) at -20℃ is ≥ 39 J, the shear area at -40℃ is ≥ 55%, and the ductile-brittle transition temperature decreases from 0℃ to -40℃.
2. The high-strength and high-toughness free-machining ferritic stainless steel as described in claim 1, characterized in that, The chemical composition, by weight percentage, includes C: 0.120%–0.150%, Si: 0.2%–0.5%, Mn: 1.20%–1.40%, P≤0.028%, S: 0.20%–0.23%, Cr: 16.10%–16.50%, Mo: 0.22%–0.30%, N: 0.035%–0.055%, with the remainder being iron and unavoidable impurities.
3. A method for preparing the high-strength and high-toughness free-machining ferritic stainless steel according to any one of claims 1-2, comprising the following steps: Electric arc furnace smelting → AOD furnace smelting → LF furnace refining → continuous casting → rolling → annealing.
4. The method for preparing a high-strength and high-toughness free-machining ferritic stainless steel according to claim 3, characterized in that, Low-P and low-toxic-elements scrap stainless steel is added to the electric arc furnace for smelting, and the P content of the tapped steel is controlled to be ≤0.028% to obtain crude steel.
5. The method for preparing a high-strength and tough free-machining ferritic stainless steel according to claim 3, characterized in that, The AOD furnace smelting process includes: adding molten steel smelted in an electric arc furnace to the AOD furnace, followed by the addition of cold lime, and using top and bottom oxygen blowing to raise the temperature and decarburize, with a target C content of 0.05% to 0.08%; reducing by adding ferrosilicon and ferromanganese alloy, controlling the slag basicity R at 1.5 to 2.0; and finally, adding ferrosulfide alloy to the molten steel according to the target sulfur content of 0.15% to 0.25% and the ferrosulfide yield, with a target tapping temperature of 1630 to 1650℃.
6. The method for preparing a high-strength and tough free-machining ferritic stainless steel according to claim 3, characterized in that, The LF furnace refining process includes: after the molten steel from AOD smelting arrives at the station, the Ar gas flow rate is adjusted. When the slag becomes fluid, samples are taken and the temperature is measured. Based on the sampling results, alloys are added to finely adjust the composition of the molten steel to obtain the target molten steel. Subsequently, the bottom soft blowing argon gas time is ≥5min to allow the inclusions to float fully. Finally, the ladle temperature is controlled at 1630~1650℃.
7. The method for preparing a high-strength and tough free-machining ferritic stainless steel according to claim 3, characterized in that, The continuous casting process includes: a target superheat of 30–50°C, a continuous casting cooling regime of "weak cooling", a casting speed set at 0.7–0.9 m / min, and a crystallizer water flow rate set at 92–95 m³ / min. 3 / h, the set value of water flow rate in the foot roller section is 2.0~3.5m³ / h. 3 / h, the set value for the clamping section water flow rate is 1.9~2.5m³ / h. 3 / h.
8. The method for preparing a high-strength and tough free-machining ferritic stainless steel according to claim 3, characterized in that, Rolling includes: The initial rolling temperature of the continuously cast billet is set at 1180~1200℃, the rolling specification is φ18mm, the roughing rolling adopts head-avoiding rolling, the Garrett coiler completes the coiling of the wire rod, and the wire rod is transferred and cooled by water after being removed from the line to obtain hot-rolled wire rod.
9. The method for preparing a high-strength and tough free-machining ferritic stainless steel according to claim 3, characterized in that, Annealing includes: The hot-rolled wire rod is rapidly heated to 720-760℃ at a rate of 10-15℃ / min and held for 180-240min, then cooled to no higher than 650℃ at a controlled rate of 50-70℃ / h.
10. The method for preparing high-strength and tough free-machining ferritic stainless steel according to any one of claims 3-9, characterized in that, The machinability of the ferritic stainless steel is as follows: the surface roughness of the sample after machining is ≤1.40μm, the chips are brittle and easily broken, with "C" shaped chips accounting for as high as 70% to 80%, and the main cutting force is ≤137N.
Citation Information
Patent Citations
Stainless steel wire rod easy to cut and manufacturing method thereof
CN106636893A
Sulfur-containing tellurium-containing free-cutting ferritic stainless steel and manufacturing method thereof
CN114182177A